СРОЧНО СРОЧНО СРОЧНО СРОЧНО СРОЧНО СРОЧНО СРОЧНО СРОЧНО СРОЧНО СРОЧНО СРОЧНО СРОЧНО СРОЧНО СРОЧНО СРОЧНО СРОЧНО СРОЧНО СРОЧНО СРОЧНО СРОЧНО СРОЧНО СРОЧНО СРОЧНО СРОЧНО СРОЧНО СРОЧНО СРОЧНО СРОЧНО СРОЧНО СРОЧНО СРОЧНО СРОЧНО СРОЧНО СРОЧНО СРОЧНО СРОЧНО СРОЧНО СРОЧНО СРОЧНО СРОЧНО СРОЧНО СРОЧНО СРОЧНО СРОЧНО ​
Ответ
4/5 (1 оценка)
1
Evgenia4836 3 недели назад
Светило науки - 5187 ответов - 23701 помощь

Ответ:

Пошаговое объяснение:

а²= а*а

а³= а*а*а

(-а)²= а²

(-а)³= -а³

1) (-11)²= 121

2) (-0,7)²= 0,49

3) (-2/5)²= 4/25

4) (-4)³= -64

5) (-0,2)³= -0,008

6) (-1/2)³= -1/8

7) (-10)²+97= 100+97= 197

8) (-0,9)²-1 = -0,81-1= -1,81

9) (-2/3)³-1= -8/27-1= -35/27